Comparison between simulations and experiment for heat transfer characteristics in the re-burning kiln heat exchanger - Piyathida Panyoyai (2020)
© 2020 Institute of Physics Publishing. All rights reserved. Waste heat from the combustion process that is left unused may cause pollution problems and adversely affect health. This waste heat should be recovered. In this research, the simulation and experimental data on heat transfer characteristics of the pipe coiled inside the re-burning kiln heat exchanger were studied. The main objective of this study was to compare heat transfer coefficients obtained from the simulation using water as the working fluid with those obtained experimentally from the re-burning kiln heat exchanger for the drying system. The re-burning kiln heat exchanger was of coil-pipe-type with an outside diameter of 38 mm. The coiled pipe set up on the re-burning kiln heat exchanger was 80 cm in width and 173 cm in height. The flow rate of the cold water used as a working fluid was varied from 10 to 20 LPM, while the surface temperature of the coil pipe was varied from 200±20°C to 400±20°C, respectively. Thermal conductivity and outlet temperature of the water were also measured as a function of the internal temperature and water flow rate. The experimental results were validated against the simulation. The results showed that when the flow rate of water inlet decreased from 20 LPM to 10 LPM, the temperature of the water outlet was increased from 52.4 °C to 76.3 °C respectively. An increase in the temperature of the water outlet because of increased the re-burning kiln heat exchanger temperature and reduced the mass flow rate of supply water. The obtained simulated heat transfer coefficient in the re-burning kiln heat exchanger was in agreement with the experimental results.